2010
DOI: 10.1038/ejcn.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

Convenience foods in children's diet and association with dietary quality and body weight status

Abstract: Background: Pre-prepared commercial foods (convenience foods, CFs) are one aspect of modern dietary habits. The present paper examines the association between CF consumption and dietary quality or body weight status in a sample of German children and adolescents. Methods: Linear mixed-effect regression analyses using data from 586 participants (296 boys, 3-18 years) in the Dortmund Nutritional Anthropometric Longitudinally Designed Study, who yearly completed 1890 3-day dietary records and anthropometric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 27 publications
1
40
1
1
Order By: Relevance
“…For instance, the DONALD study 35 indicated a small but positive association between consumption of high-energy foods and body weight among boys (b ¼ 0.104, P ¼ 0.0098). Another Japanese study 36 observed a lower BMI among those adolescents with a 'healthier' DP and a higher BMI among those with 'western' DP.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the DONALD study 35 indicated a small but positive association between consumption of high-energy foods and body weight among boys (b ¼ 0.104, P ¼ 0.0098). Another Japanese study 36 observed a lower BMI among those adolescents with a 'healthier' DP and a higher BMI among those with 'western' DP.…”
Section: Discussionmentioning
confidence: 96%
“…CF with high energy density and the change in %BF in children and adolescents within a study period of 5 years (3) . In contrast to the present examination the association between high-energy CF and %BF was significant only for boys.…”
Section: Discussionmentioning
confidence: 99%
“…This focus on improving CS and FS can be partly attributed to the increasing rhetoric around the decline of cooking skills and parallel rise in consumption of convenience foods; where convenience products are typically considered to be of poorer nutritional quality and higher energy content when compared to home prepared and home cooked meals (Gillman, Rifa-Shiman, Frazier, et al, 2000). Indeed studies have shown positive associations with consumption of convenience foods and increases in body composition indices such as body mass (Alexy et al, 2011;Cornelisse-Vermaat & van den Brink, 2007), highlighting food preparation and cooking as key intervention targets. However, most interventions designed to improve diet quality by way of increasing CS and FS were unsuccessful when evaluated in these terms.…”
Section: Discussionmentioning
confidence: 99%